2018
DOI: 10.1007/s00244-018-0583-1
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Concentrations in Sentinel Fish Exposed to Contaminated Sediments Under a Natural Recovery Strategy Within the St. Lawrence River Area of Concern at Cornwall, Ontario, Canada

Abstract: Legacy mercury (Hg) sediment deposits are a long-term issue within the St. Lawrence River (Cornwall) area of concern with three depositional areas along the Cornwall, ON waterfront containing sediments that exceed the Ontario Sediment Quality Guidelines for Hg. Assessing the bioavailability of these Hg-contaminated sediments plays a crucial role in evaluating the effectiveness of the Cornwall Sediment Strategy based on a natural recovery approach. We collected specimens of fallfish (Semotilus corporalis), roun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…In the CSS region, high sedimentary Hg concentrations have been positively correlated with concentrations of MeHg in benthic invertebrates (amphipods) in zone 1 (Razavi et al 2013), where elevated concentrations of Hg have also been found in spottail shiners (Choy et al 2008) and yellow perch (Fowlie et al 2008), as well as fallfish and round gobies (Lapointe and Ridal 2019). Surficial sediments have also been found to be enriched in MeHg in these areas (Delongchamp et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the CSS region, high sedimentary Hg concentrations have been positively correlated with concentrations of MeHg in benthic invertebrates (amphipods) in zone 1 (Razavi et al 2013), where elevated concentrations of Hg have also been found in spottail shiners (Choy et al 2008) and yellow perch (Fowlie et al 2008), as well as fallfish and round gobies (Lapointe and Ridal 2019). Surficial sediments have also been found to be enriched in MeHg in these areas (Delongchamp et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This elevated surficial Hg is likely being released into the overlying water and acting as a source of bioavailable Hg to local biota (Delongchamp et al 2010). Although MeHg is a relatively small component of the total Hg signal in these sediments (<10%; Delongchamp et al 2010), as it bioaccumulates up the food web it forms a greater proportion of the Hg signal, reaching an average of 41% of the Hg signal in amphipods (Razavi et al 2013) and upwards of 80% or more in young‐of‐the‐year fish (Lapointe and Ridal 2019). Whereas many local biota have been shown to be enriched in Hg at sites with high sedimentary Hg concentrations, some have failed to find a relationship between sedimentary Hg and Hg in resident biota (both invertebrates and fish; Hodson et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation